(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
During the acute period of hemorragic stroke, patients with diabetes and early rehabilitation measures were carried out, and 70 patients with hemorragic stroke and diabetes without early rehabilitation measures were examined. All patients underwent subjective, objective, clinical-instrumental examinations, and the effectiveness of the early rehabilitation process was studied in patients with diabetes and in groups without diabetes.